Sintesis Silika Gel dari Abu Sekam Padi Termodifikasi Kitosan serta Aplikasinya sebagai Adsorben Methylene blue - Harum Widyastuti; Aman Sentosa Panggabean; Dirgarini Julia Nurlianta Subagyono (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
ABSTRACT Synthesis of silica gel from chitosan-modified rice husk ash and its application as an adsorbent of methylene blue have been studied. The stages of this research included the preparation of rice husk samples, the synthesis of silica ash of rice husks, sodium silicate, chitosan solution, and synthesis of silica gel - chitosan - tripolyphosphate, and the characterization of silica gel material from chitosan-modified rice husk ash. The results showed that silica gel adsoerben from chitosan modified rice husk ash was able to adsorb methylene blue dyes with an optimum pH of 5, optimum contact time for 60 minutes and adsorption capacity of 16.4554 mg/g. Keywords: rice husk, silica gel, chitosan, methylene blue.